Gogol's crime and punishment: an essay in the interpretation of Nikolai Gogol's "Dead souls" - Heftrich, Urs (Studies in Russian and Slavic literatures, cultures, and history, 2022)
Introduction: Of Beauty, Truth, and Evil -- Part One: Chichikov's Prehistory -- Ethos and Epic -- The Ground Plan of Dead Souls -- The Ground Plan of Dead Souls Revisited -- Part Two: Chichikov's Crime -- On Truth and Lies in a Moral Sense -- The Five Faces of Lying -- In the Shadow Realm of Lies -- Part Three: Chichikov's Punishment -- Judgment and Rumor -- The Five Acts of the Drama -- Ethos and Epic: Chichikov's Crime and Punishment.